Bimbingan Kelompok Experiential Learning dan Dampaknya Terhadap Kemampuan Komunikasi Interpersonal - Mohamad Rizal Pautina; Jumadi Mori Salam Tuasikal (LP2M IAIN Sultan Amai Gorontalo, 2022)
ABSTRACTThe purpose of this study was to determine the effectiveness of experiential learning group guidance services in improving Communication Interpersonal skills. The research method used is quantitative research with pre-experimental research methods using One Group Pretest - Posttest Design. The population in this study were 200 students of the Guidance and Counseling Department, State University of Gorontalo. Then the sampling using purposive sampling technique as many as 15 people. The instrument used was a Communication Interpersonal skills assessment questionnaire prepared using a likert scale which was declared valid with a reliability score of 0.95. The data analysis technique was carried out by means of a nonparametric statistical test using the Wilcoxon test. The results showed that in the positive ranking data there was an increase in the mean rank with a score of 4 and the results of the number of ranks were 28 with a significance of 0.018 < 0.05, which means that there was a significant difference in the pre-test and post-test data scores. The results of these statistical tests can indicate that the experiential learning bimbingan kelompokservice is effective for improving Communication Interpersonal skills in guidance and counseling students of Gorontalo State University.